Application of Advance Research Tools in Phytopharmaceutical Adulteration and Authentication: The ‘Omics’ Approach - Kalaivani, Muthusamy; Chaudhary, Priyanka; Raghuvanshi, Rajeev Singh (Pharmacognosy Reviews)
Traditional medicines are the basis of plant derived natural products including extracts, fractions, essential oils and active chemicals. From past decade plant derived products become a primary choice for biological and pharmacological research and contribute for the development of various synthetic and semi-synthetic drugs worldwide. Assurance of the safety, quality and efficacy of phytopharmaceuticals has now become a crucial point throughout the world. The present review is focused about the ‘omics’ approaches towards the identification of any adulteration and maintenance of the quality of phytopharmaceuticals. DNA and RNA based genomics and metabolomics profiling of phytopharmaceuticals have been successfully used for the chemical analysis, characterization and quality control of herbal medicines because of their accuracy and reliability. In this regard, present review discusses the potential usage of various advanced biotechniques like DNA fingerprinting, Next Generation Sequencing, Epigenetic profiling, metabarcoding, chemometrics, Single Nucleotide Polymorphism analysis to authenticate the plant based medicines.
Keywords: Phytopharmaceuticals; Genomics; Metabolomics; Chemometrics; Epigenetic profiling